Making a case for universal and targeted children's occupational therapy in the United Kingdom. (July 2016) - Hutton, Eve; Tuppeny, Sharon; Hasselbusch, Andrea
This article makes the case for increasing the reach and the impact of children's occupational therapy in the United Kingdom, through inclusion of universal and targeted services alongside specialist provision. It is proposed that achieving a greater balance between these different levels or tiers of provision can promote the health, well-being and participation of all children, including those with additional needs. During a time of austerity, we argue that a broader offer also distributes finite public resources more effectively – potentially reducing pressure on scarce specialist resources. Sustainable options for meeting greater population need are proposed and occupational therapists are encouraged to evaluate the effect of changing the balance of provision to inform future commissioning.